Current considerations for heart-kidney transplantation - Ahsan, Syed Adeel; El Nihum, Lamees I.; Arunachalam, Priya; Manian, Nina; Al Abri, Qasim; Guha, Ashrith (Frontiers in Transplantation, 2022)
Cardiorenal syndrome is a complex syndrome characterized by dysfunction of the heart and kidneys in an interdependent fashion and is further divided into different subtypes based on primary organ dysfunction. Simultaneous Heart-Kidney transplantation is the treatment of choice for end-stage irreversible dysfunction of both organs, however, may be avoided with determination of cardiorenal subtype and management of primary organ dysfunction. This article discusses types of cardiorenal syndrome, indications and concerns regarding the use of simultaneous heart-kidney transplantation, and outlines algorithms for determination of need for dual vs single organ transplantation.